KOORDINASI LEMBAGA MILITER DAN PEMERINTAH DALAM PENGELOLAAN ASET TANAH MILITER: STUDI SENGKETA LAHAN DI LANUD HUSEIN SASTRANEGARA BANDUNG - Gumilang, Mugi; Sudirman, Arfin; Herdiansyah, Ari Ganjar (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The Indonesian Air Force (TNI AU), which is the main component of air defense, has an organization equipped with human resources, regulations, and material resources, which legally includes assets referred to as State-Owned Goods (BMN). The assets can be classified as fixed assets and other assets. Fixed assets can further be divided into two categories: movable assets and immovable assets. Currently, the management of military land assets is still chaotic, including land assets that are classified as State Property (BMN) at Husein Sastranegara Air Base in Bandung. (Lanud Husein). To this end, a study was conducted aimed at analyzing the institutional cooperation between the Air Force and local/central government in asset management, specifically the management of state-owned assets at Husein Sastranegara Air Force Base in Bandung. Additionally, it analyzes the cooperation currently being undertaken by the Air Force and local/central government for the security of Air Force land assets at Husein Sastranegara Air Force Base within the framework of good governance. This research uses a qualitative method with descriptive narration, where the data sources come from interviews with several informants and data collection from documents. The research results indicate that the institutional cooperation between the Air Force (TNI AU) at Husein Sastranegara Air Base and the ATR BPN as well as the local DJKN/KPKNL in the management of state assets shows that efforts have been made to enhance asset management effectiveness. Although progress has been made, there are still obstacles such as differences in the value of state asset utilization rates, a lack of personnel, and insufficient training. However, the management of land assets of the Indonesian Air Force at Husein Sastranegara Air Base has aligned with the fundamental concepts of asset management, which include planning, organizing, utilizing, maintaining, and disposing of assets.